KEDUDUKAN ANAK DALAM PENOLAKAN ITSBAT NIKAH MENURUT UNDANG - UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (STUDI KASUS PENETAPAN NOMOR 0030/PDT.P/2013/PA.TSE) - Chandra, Bobby; Lestari, Rika; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Registration of marriage was very large maslahahnya to mankind, especially in the era of globalization as it is today. The elements that are not recorded marriages because they may be troubled marriages, the couple did not have a valid marriage certificate, for it need reaffirm the marriages already performed more commonly known by the term attestation of marriage. Some of the problems that arise are clashes in the aspects of Islamic marriage laws with national laws due to marriage under the hand, as a result status of children born in such marriages are not clear. As in a rejection attestation of marriage determination once knowl-separation of children in the Religious Court Tanjung Selor with number 0030 / Pdt.P / 2013 / PA.Tse. The purpose of this thesis, namely; First, to determine the position of the child in attestation of marriage rejection of marriage according to Law No. 1 of 1974 About Marriage, second, to determine Determination Number 0030 / Pdt.P / 2013 / PA.Tse provide legal certainty to the rights of children born out of marriage that attestation of marriage rejected by the court. The author uses a normative legal research is a study conducted by examining the legal materials of libraries or secondary data.From the research problem there are two main things that can be inferred. First, Position the child in ithbat rejection as a child outside marriage analogous to marry because it does not comply with Article 42 of Law No. 1 of 1974 on Marriage and the absence of regulation of ithbat marriage in Act No. 1 of 1974 on Marriage though children born out of marriage were canceled but because the position of the child before the rejection of marriage as a child ithbat beyond mating then the position of the child remains a child outside of marriage.Second, The rule of law on the rights of children in Determination No. 0030 / Pdt.P / 2013 / PA.Tse can be met with the jurisprudence as a source of law for children to claim their rights of parents admit that where the form of the right to a name parents, legitimate children's inheritance rights, the right to earn a living, the right to a guardian of marriage of the parents if their daughtersKeywords: Ratification of-Marriage-Kids